Kemampuan Literasi Numerasi Siswa Kelas 3 SD Pada Materi Operasi Hitung Bilangan Cacah - Nazaruddin, Ilham; S, Ronald Mahmud; Sari, Ery Novita; Sundariany, Sundariany; Fitriyani, Fitriyani (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2026)
The purpose of this study was to determine the numeracy literacy skills of 3th grade students in the material of arithmetic operations of whole numbers. This study used a descriptive method with a qualitative approach. This study was conducted on 10 3th grade students of SDN 101739 Sei Mencirim. The data collection technique used was a test instrument in the form of literacy-based story questions given to 10 research subjects to determine students' numeracy literacy skills, interviews conducted with students and also interviews with 3th grade elementary school homeroom teachers as supporting data about students' numeracy literacy skills. Based on the results of the study that has been conducted on 20 students, the following results were obtained: 1) 5 out of 10 students have a low level of numeracy literacy skills because they get a score below 65, 2) 4 out of 10 students have a medium level of numeracy literacy skills because they get a score below 85, and 3) 1 out of 10 students has a high level of numeracy literacy skills because they get a score above 85.